2015
DOI: 10.5923/j.ijme.20150504.03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Modulus of Elasticity in Damaged Wooden Beams

Abstract: This research aimed to employ two methods of calculation to obtain the bending modulus of elasticity in wooden specimens of Paricá (Shizolobium amazonicum), a simplified, adapted from the Brazilian standard ABNT NBR 7190, and another alternative based on the least squares method, in order to compare the efficiency of both. Therefore, some defects in wood specimens were created, based on the combination between the positions of the rips (damage) along the axis of the pieces (8.63, 17.25 and 25.86 cm) and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A good way to begin an inspection for decay is a visual inspection technique search for decay manifestations, emphasizing locations or conditions most conducive to prolonged wetting [12][13][14][15].…”
Section: Inspection Techniques To Assess Timber Structuresmentioning
confidence: 99%
“…A good way to begin an inspection for decay is a visual inspection technique search for decay manifestations, emphasizing locations or conditions most conducive to prolonged wetting [12][13][14][15].…”
Section: Inspection Techniques To Assess Timber Structuresmentioning
confidence: 99%
“…Therefore, by the binding legal requirements of the countries, only wood with a designated strength class can be used for applications in the construction sector. Thus, it is aimed to ensure both structural safety and economical use of the material (Faria et al 2012;Christoforo et al 2015;Ridley-Ellis et al 2016;Burawska-Kupniewska et al 2020;Krzosek et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other relevant study [14] have examined two methods of calculation to obtain the bending modulus of elasticity in wooden specimens of Paricá (Shizolobium amazonicum) with some defects created: a simplified, adapted from ABNT NBR 7190: 1997, and another based on the least square method. Results of the confidence intervals showed that de modulus of elasticity for both ways of calculation were equivalent for non-defective specimens.…”
Section: Introductionmentioning
confidence: 99%